Efficacy and feasibility of snare-assisted endoscopic resection of small submucosal gastric tumors: A retrospective analysis - Zhao, Fei; Liu, Zhenzhen; Wei, Anwei; Wang, Wei; Xu, Na; Pu, Xuanmei; Ullah, Saif (Frontiers in Oncology, 2022)
Background and Aim: The prevalence of small submucosal gastric tumors is rising. Despite the fact that high success rate of endoscopic resection of small submucosal gastric tumors originating from the muscularis propria has been reported, the procedure is technically challenging and has a high rate of complications. In this study, we investigated the efficacy and feasibility of a novel snare assisted endoscopic resection technique for small submucosal gastric tumors. Patients and Methods: This is a single center consecutive study of 60 patients who were diagnosed with small submucosal gastric tumors originating from the muscularis propria and subsequently underwent snare-assisted endoscopic resection between January 2019 and January 2021 at our hospital. Data on the demographics characteristics, procedural success rate, complications, recurrence rate, and histopathology of the resected specimen were collected and analyzed retrospectively. Results: The majority of the patient’s population were male (66%) with the mean age of 48.4 ± 9 years (range: 20-70 years). The mean size of the tumor confirmed by endoscopic ultrasonography was 6.4±1.6 mm (range: 3.1-9.8 mm). All the tumors were resected successfully using endoscopic snare assisted endoscopic resection technique. The mean procedure time was 22.8±9.6 (range: 15-35 minutes). The procedure technical (performed the procedure successfully without converting to surgery) and clinical success (the patient fully recovered after the procedure without experiencing any complications) rate was 100%. Eighteen (24%) patients had very small amount of mucosal damage and wound closure were not needed in these patients. During 6-24 months of follow up, no recurrence or metastasis occurred. No adverse event noted during the follow up time. Conclusion: The novel approach of snare assisted endoscopic resection is simple, feasible and effective for tumors with small size and originating from the gastric muscularis prorpia. In addition, it offers a better alternative therapy for the complete resection of small submucosal gastric tumors. Its advantages compared with traditional endoscopic approaches such as endoscopic submucosal resection and endoscopic submucosal dissection include shorter procedure times, less costly, and a low rate of complications (perforation, bleeding and infection).